Information Retrieval--A View of its Past, Present, and Future - Meadow, Charles T. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The development of information retrieval systems is reviewed from its early history to the present time. Emphasis is placed on user languages and functionality and the effect of available technology on these aspects. Through most of its history, retrieval has depended on the use of surrogate records because technology did not permit direct searching of documents.